ANALISIS STRATEGI PENGEMBANGAN UMKM KOTA BEKASI BERBASIS RT RW - Najmulmunir, Nandang (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2009)
Micro, small and medium enterprises (UMKM) of Bekasi City have to be a leader in theregional economic developmen, because of there are many competitive commodities,such as doll, food and beverages, handycraft, etc. The development strategies foraccelarating them are the diversive strategies. How to overcome the many treats andmaking innovation for product diversification and market penetration. Key ward: Micro, small and medium enterprise, diversive development strategies,inovation and penetration.